2005
DOI: 10.1002/cncr.21578
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of voice therapy in patients after treatment for early glottic carcinoma

Abstract: CD3/CD20 immunostains are often performed in the initial cytological evaluation of lymphoid‐rich pleural effusions (LR‐PE). Most benign LR‐PE are predominantly composed of T(CD3+) cells while most malignant LR‐PE are of B(CD20+) cell lineage. As part of the effort to contain laboratory costs and improve diagnostic accuracy, there is increasing interest in applying principles of evidence‐based pathology to the use of immunostains. In this retrospective study, we reviewed the effectiveness of CD3/CD20 immunostai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 137 publications
2
66
0
5
Order By: Relevance
“…Another non-statistical approach to deWne a clinically relevant diVerence score to be used in group design studies is to line up published studies on the eYcacy of voice treatment and assess diVerence score appearing to be signiWcant or non-signiWcant. Four studies on the eYcacy of voice therapy in patients with several benign voice pathologies or voice pathologies following treatment for glottic malignancy, showed signiWcant improvement of the mean VHI with a range of 12 to 18 points [10,14,15,23]. On the contrary, Speyer [18] reported a non-signiWcant median improvement of 6 points after voice therapy in patients with a diversity of chronic benign voice disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another non-statistical approach to deWne a clinically relevant diVerence score to be used in group design studies is to line up published studies on the eYcacy of voice treatment and assess diVerence score appearing to be signiWcant or non-signiWcant. Four studies on the eYcacy of voice therapy in patients with several benign voice pathologies or voice pathologies following treatment for glottic malignancy, showed signiWcant improvement of the mean VHI with a range of 12 to 18 points [10,14,15,23]. On the contrary, Speyer [18] reported a non-signiWcant median improvement of 6 points after voice therapy in patients with a diversity of chronic benign voice disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies include patients with and without deviant voice quality and mean VHI data are therefore not informative on the amount of problems that patients with voice impairment after oncological treatment encounter in daily life. In a study on 23 patients with voice problems after oncological treatment, Van Gogh et al [23] reported a mean VHI score of 35. However, interpretation of how cancer patients cope with voice problems compared to patients with voice problems due to benign laryngeal lesions and compared with the normal population is diYcult because of some underexposed psychometric characteristics of the VHI: data from the normal population are limited, no clear clinical cut-oV score is available, and information on clinical relevant diVerence scores is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Each voice quality is rated on a four-point scale, where 0 ¼ normal, 1 ¼ mildly impaired, 2 ¼ moderately impaired and 3 ¼ severely impaired. The vocal fry parameter (rated on a four-point scale mirroring the GRBAS) was added to the rating protocol as it has also been reported in irradiated voices [12,13].…”
Section: Perceptual Analysesmentioning
confidence: 99%
“…The VHI was translated into Dutch and a cutoff score indicating voice problems in daily life was determined as a total VHI score >14. 9 The VHI has been translated and validated into several languages, including Dutch, and the various versions are proven to be equivalent. 10 …”
Section: Voice Handicap Indexmentioning
confidence: 99%